1998
DOI: 10.1016/s0042-6989(97)00443-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of trichromacy in primates

Abstract: Although trichromacy in Old and New World primates is based on three visual pigments with spectral peaks in the violet (SW, shortwave), green (MW, middlewave) and yellow-green (LW, longwave) regions of the spectrum, the underlying genetic mechanisms differ. The SW pigment is encoded in both cases by an autosomal gene and, in Old World primates, the MW and LW pigments by separate genes on the X chromosome. In contrast, there is a single polymorphic X-linked gene in most New World primates with three alleles cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 24 publications
3
104
0
5
Order By: Relevance
“…The tree shrew genome encompasses the orthologues of almost all the 209 known visually related human genes, but lacks two cone photoreceptors, the middle wave-length sensitive proteins, which are specifically duplication genes in catarrhines and lead to the trichromacy in higher primates 28 . The absence of the middle wave-length sensitive proteins is consistent with the fact that tree shrews, similar to some lower primates, lack the green pigment and possess dichromats 29 . As most tree shrew species are diurnal and spend the entire night for sleep in their nests, they do not rely on dim-light visuals 29 .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The tree shrew genome encompasses the orthologues of almost all the 209 known visually related human genes, but lacks two cone photoreceptors, the middle wave-length sensitive proteins, which are specifically duplication genes in catarrhines and lead to the trichromacy in higher primates 28 . The absence of the middle wave-length sensitive proteins is consistent with the fact that tree shrews, similar to some lower primates, lack the green pigment and possess dichromats 29 . As most tree shrew species are diurnal and spend the entire night for sleep in their nests, they do not rely on dim-light visuals 29 .…”
Section: Resultssupporting
confidence: 74%
“…The absence of the middle wave-length sensitive proteins is consistent with the fact that tree shrews, similar to some lower primates, lack the green pigment and possess dichromats 29 . As most tree shrew species are diurnal and spend the entire night for sleep in their nests, they do not rely on dim-light visuals 29 . The evolutionary rate testing suggested that the rod photoreceptor rhodopsin, which is responsible for the night vision, had a faster evolutionary rate in the tree shrew lineage (Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…We presume that, at a certain point in human evolution, ancestral species may have relied more on visual and auditory signals, rather than on chemical signals, for communicating social and reproductive status. Remarkably, it is at the time in evolution when selective pressure on TRPC2 is relaxed that the common ancestor of OW monkeys and apes developed trichromatic color vision through a gene duplication of the green͞red opsin gene (32,33). Indeed, many species of OW monkeys signal sexual and social status via colorful skin pigmentation of the face or genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied signal/receiver systems in this regard is the color vision of insect pollinators and the flowers with which they interact (Chittka 1996;Chittka 1997;Chittka and Briscoe 2001 The evolutionary history we are trying to untangle is potentially paralleled not only by insects and flowers. Similar scenarios may be proposed, for instance, for primates and fruit; did trichromacy evolve in primates to aid in detecting and selecting ripened fruit (Hunt et al 1998;Mollon 1989;Osorio and Vorobyev 1996;Regan et al 1998;Smith et al 2003), or did fruit color evolve to attract seed dispersers more effectively? Our proposal that the relevant component of variation in throat color should be represented along a line through color space may provide useful insight into many such similar questions concerning the evolution of signals and receivers.…”
Section: Generalmentioning
confidence: 90%